EFFECT ANTHOCYANIN OF PURPLE POTATO GUNUNG KAWI ON MDA LEVELS, EXPRESSION OF CASPASE-3, AND SPATIAL MEMORY FUNCTION ON DIABETIC WISTAR RATS - Prabawati, Risma Karlina; Ratnawati, Retty; Rahayu, Masruroh; Prakosa, Ardani Galih (Malang Neurology Journal, 2019)
Background: Hyperglycemia condition will decline cognitive function. No basic therapy has been 2 found for this. Purple potato anthocyanins are useful as anti-inflammatory, antioxidant, neuroprotectant, and antidiabetic.Objective: Evaluate effect of purple potato’s anthocyanins on MDA levels, brain’s caspase-3 expressiom, and spatial memory function in diabetic model of Wistar rats.Methods: This is an experimental study using diabetic model rats. The sample was divided into negative and positive control, anthocyanin dose of 10 mg/kg, 20 mg/kg, and 80 mg/kg groups. MDA levels were measured using spectrophotometer, caspase-3 expression with immunohistochemistry, and spatial memory function using Morris water maze test.Results: Tukey test showed that anthocyanin 10, 20, and 80 mg/kg lowering MDA levels, caspase-3 expression, and Morris water maze’s travel time compared to control positive (p = 0.000). But anthocyanin 80 mg/kg make a significant increase on these three variabels compared to 10 and 20mg/kg groups (p = 0.010). Pearson test showed that there no correlation between anthocyanin’s dose, MDA levels, caspase-3 expression, and Morris water maze test.Conclusion: Anthocyanin doses 10 and 20 mg/kg lowering MDA levels and caspase-3 expression, also improves spatial memory function on diabetic model of Wistar rats.